2015
DOI: 10.1107/s2053230x1402617x
|View full text |Cite
|
Sign up to set email alerts
|

Structures ofDrosophila melanogasterRab2 and Rab3 bound to GMPPNP

Abstract: PDB references: Rab3, 4rkf; Rab2, 4rke Rab GTPases belong to the large family of Ras proteins. They act as key regulators of membrane organization and intracellular trafficking. Functionally, they act as switches. In the active GTP-bound form they can bind to effector proteins to facilitate the delivery of transport vesicles. Upon stimulation, the GTP is hydrolyzed and the Rab proteins undergo conformational changes in their switch regions. This study focuses on Rab2 and Rab3 from Drosophila melanogaster. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…And, although of fundamental importance, remained our understanding of the cell biological origin and molecular mechanics of presynaptic precursor biogenesis fragmentary. We here provide evidence, that in an early step of precursor biogenesis synaptic proteins sort out of the secretory trans-Golgi through independent routes on early, small and tubular membranous vesicles, a process clearly regulated by the small Golgi-related and highly conserved GTPase RAB2 (Chan et al, 2011;Lardong et al, 2015;Liu and Storrie, 2012;Lorincz et al, 2017;Saraste, 2016;Tisdale and Balch, 1996).…”
Section: Discussionmentioning
confidence: 70%
“…And, although of fundamental importance, remained our understanding of the cell biological origin and molecular mechanics of presynaptic precursor biogenesis fragmentary. We here provide evidence, that in an early step of precursor biogenesis synaptic proteins sort out of the secretory trans-Golgi through independent routes on early, small and tubular membranous vesicles, a process clearly regulated by the small Golgi-related and highly conserved GTPase RAB2 (Chan et al, 2011;Lardong et al, 2015;Liu and Storrie, 2012;Lorincz et al, 2017;Saraste, 2016;Tisdale and Balch, 1996).…”
Section: Discussionmentioning
confidence: 70%
“…To investigate the molecular mechanism by which Rab3 functions to control the protein composition of individual active zones we performed a mutational analysis of Drosophila Rab3. Rab3 is highly conserved between flies and rodents both in terms of amino acid sequence (78% sequence identity with mouse Rab3a [ 28 ]; Fig 1A ) and protein structure [ 29 ]. Previous studies have identified specific residues of rodent Rab3 required for its roles in the regulation of exocytosis and the trafficking of synaptic vesicles [ 28 , 30 – 34 ].…”
Section: Resultsmentioning
confidence: 99%
“… (A) Sequence alignment of Drosophila Rab3 with mouse Rab3a. Amino acid numbers and labels for secondary structures (green, β-strands; blue, α-helices) and switch regions (pink) are shown for Drosophila Rab3, as determined by crystal structure analysis of fly Rab3 [ 29 ]. CDR region labels (yellow) correspond to the RabCDRs identified in rodent Rab3 [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural biology of Rabs and their related regulators and effectors is largely unexplored for Leishmania. Although a number of crystal structures of Rab proteins from different organisms have been reported (29)(30)(31)(32)(33)(34)(35), no structure for any of the Rab proteins from Leishmania has been determined so far. Although conventional Rab5 effectors like EEA1, Rabex5, Rabaptin5, and Rabenosyn5 have been well characterized in mammalian cells, their homologs have not been identified in Leishmania (15).…”
Section: Introductionmentioning
confidence: 99%